Protocol for a cluster-randomized control trial of a remote workplace resilience intervention for early care and education providers: The OnWARD trial - Derek Hales; Regan Burney; Erik Willis; Emmy Clarke; Sarah Peterson; Shakiera Branch; Brandon Fowlin; Sherry Chesak; Lara A. Linnan; Amit Sood; Nazaret C. Suazo; Deborah J. Jones (PLoS ONE, 2026)
Work-related stressors take a toll on individuals’ health and well-being, a toll which is often heavier for under-resourced, low-paid segments of the essential workforce who serve our communities. Resilience programs have arisen as a promising workplace strategy to improve mental health and well-being. However, emerging programs are constrained by time and resource-intensive implementation strategies that are challenging to scale for marginalized segments of the workforce, including early childcare education (ECE) staff. The goal of this 15-month cluster randomized control trial is to compare change in resilience assets and resources for ECE staff in centers (n = 80 consisting of 640 ECE workers) randomly assigned to either a remotely delivered resilience (intervention) or physical activity (attention control) program. Measures will be collected at four timepoints: baseline (0 months), post-intervention (3 months), and long-term maintenance (9 and 15 months). Secondary outcomes will include changes in well-being, physical activity, organizational support, absenteeism, and turnover. Additionally, we will explore potential moderators of the treatment effects. The RE-AIM Framework will be used to determine the potential for individual (staff) and organizational (center) level reach, adoption, implementation, and maintenance of the two programs. Results will fill key gaps of prior resilience work by focusing on an underserved population in critical need of well-being resources with implications for the feasibility and impact of remote programming in other segments of the workforce. Trial Registration: This trial is registered with the ClinicalTrials.gov registry (NCT06919952) and approved by the Institutional Review Board (IRB) at the University of North Carolina at Chapel Hill (IRB# 25−0016).